Desarrollo de la ingeniería conceptual de una planta de producción de biodiesel a condiciones supercríticas para la empresa Proptelma (2018)
The following document presents the methods and procedures for the development of the degree project, in which it is intended to make a conceptual design of the production of biodiesel to supercritical conditions at the laboratory level in the company Proplma which is located in the municipality of Tocancipa Cundinamarca. The study was conducted in order to take advantage of the hydrocarbons market in Colombia and the country does not have the capacity to achieve low prices, so the global participation is low. The demand for biodiesel in Colombia is high for what is production is not enough for sales, additionally for biofuel production for new opinions in Colombia being pioneers for the company Proptelma in the implementation of this process.